Novel cobalt-free Pr2Ni1-xNbxO4 (x = 0, 0.05, 0.10, and 0.15) perovskite as the cathode material for IT-SOFC. (23rd March 2021) - Han, Zhiying; Bai, Jinghe; Chen, Xu; Zhu, Xiaofei; Zhou, Defeng
Abstract: The cobalt-free cathode materials with high activity is critical to the commercial application of medium temperature solid oxide fuel cells (IT-SOFC). Herein, a series of cobalt-free Nb-doped Pr2 Ni1- x Nb x O4 ( x  = 0, 0.05, 0.10, and 0.15) perovskite oxides were successfully prepared, and the effects of Nb-doping on the structure, thermal stability and electrochemical properties of the cathode material are studied in detail. The Pr2 Ni1- x Nb x O4 exhibits a K2 NiF4 type structure with Fmmm space group. The Nb 5+ cations that doped into Pr2 NiO4 replaces the Ni site, which increases the surface oxygen content, then effectively eliminates the phase transition of Pr2 NiO4 and significantly improves the ORR catalytic activity. The Pr2 Ni0.9 Nb0.1 O4 was found to occupy the lowest polarization resistance of 0.057 Ω cm 2, and the peak power density of single cells supported by the electrolyte is 0.576 W cm −2 at 700 °C, which has good long-term stability. Graphical abstract: Image 1 Highlights: The structure and performance of the cobalt-free Pr2 Ni1- x Nb x O4 cathodes are studied. Nb-doping can eliminate the phase change and improve the stability of the structures. Nb-doping can increase the ORR activity of the Pr2 Ni1- x Nb x O4 cathode. Pr2 Ni0.9 Nb0.1 O4 cathode exhibits a low polarization resistance of 0.057 Ω cm 2 . The highest peak power density is 0.576 W cm −2 at 700 °C with Pr2 Ni0.9 Nb0.1 O4 cathode.